The Profil Klinis dan Epidemiologi Pasien Covid-19 di Sukoharjo - Muhammad Rasyid Ridho; Coana Sukmagautama; Frieska Dyanneza (Plexus Medical Journal, 2022)
Introduction: The COVID-19 pandemic is still a very important concern in various parts of the world. The disease that infects the respiratory tract does have similar characteristics to SARS and MERS, but increases sporadically in various regions. Therefore, this study aims to conduct research on clinical profiles of COVID-19 patients at UNS Sukoharjo Hospital. Methods: This research is a descriptive observational study with a cross sectional approach. The population in this study were patients with confirmed COVID-19 at UNS Sukoharjo Hospital for the period December 2020 to May 2021, aged more than 18 years and had no incidents. The data obtained are then sorted based on the criteria and analyzed using descriptive analysis. Results: Based on the results of the study, the number of samples was 469 with the following characteristics: (1) the most age group was 46 – 59 (40.3%); (2) male 53.9% and female 46.1%; (3) the most confirmed jobs are private employees; (4) the most common symptoms were cough (69.9%), shortness of breath (66.5%0, and fever (62.4%);(5) the most common comorbidities were hypertension (29.6%) followed by diabetes mellitus (28.6%); (6 ) Complete blood counts generally have a normal average, while blood sugar, laboratory related to kidney, liver, D-Dimer, and CRP have an average above normal, and ALC below normal, (7) the mortality rate is 22.4%; (8) 98.1% of cases had pathological thorax readings, 81.6% pneumonia, (9) mean length of negative conversion of patients 11.28 days. Conclusion: The clinical and epidemiological profiles of COVID-19 patients at UNS Hospital as a whole have similarities with data in Indonesia as a whole and several other countries. Keywords: Clinical Profile; COVID-19; Epidemiology; UNS Hospital